Analysis of lifestyle factors in patients with concomitant chronic pancreatitis and liver cirrhosis - Aghdassi, Ali; Schneider, Alexander (Pancreatology, 2017)
Background & objectives: Chronic pancreatitis (CP) and liver cirrhosis (LC) are common gastroenterological disorders but their co-incidence is considered to be rare. This study was designed to identify lifestyle factors that are associated with the development of concomitant LC in patients with CP. Methods: In a retrospective case-control study between 2000 and 2005 122 patients with both CP and LC and 223 matched control patients with CP and no known liver disease were identified in 11 European university medical centers. Another 24 patients and 48 CP controls were identified in the period between 2006 and 2012. Results: Alcoholism was most commonly regarded as aetiology for both CP (82.2%; 95% confidence interval (CI): 75.0-88.0%) and LC (79.5%; 95% CI: 72.0-85.7%) as compared to controls with CP only (68.6%; 95% CI: 62.7-74.1%). The preferred type of alcoholic beverage and pattern of alcohol intake were the only significant lifestyle factors in multivariate analysis. Frequency of alcohol intake (p = 0.105) and smoking status (p = 0.099) were not significant in bivariate analysis and dropped out of the multivariate model. Recurrent and chronic pancreatic pain was observed more often in patients with only CP, whereas gallstones were more common in individuals with both chronic disorders. Conclusions: These findings indicate that certain lifestyle factors might be important for the development of concomitant CP and LC. More studies will be needed to identify additional genetic and environmental factors underlying this association.